Inhibition of Amphotericin B (Fungizone) Toxicity to Cells by Egg Lecithin-Glycocholic Acid Mixed Micelles - Brajtburg, Janina (1990)
Mixed micelles prepared from egg lecithin and the sodium salt of glycocholic acid markedly inhibited amphotericin B toxicity to mammalian cells without significantly affecting the antifungal effects of the drug.